Practices and resilience of dieticians during the COVID-19 pandemic: a national survey in the United Arab Emirates - Farah Naja (BMC, 2021)
Abstract Background The COVID-19 pandemic impacted the practices and resilience of most healthcare workers, including dieticians. In addition to offering critical care to COVID-19 patients, dieticians play a major role in preventing and managing conditions known to affect COVID-19, such as obesity and metabolic disorders. The objective of this study was to examine the conditions and changes in the work environment as well as resilience and its correlates among dieticians during the COVID-19 pandemic in the United Arab Emirates (UAE). Methods A cross-sectional national survey was conducted among dieticians practicing in the UAE (n = 371), using a web-based questionnaire. The questionnaire addressed, in addition to the sociodemographic information, the practice-related characteristics and resilience of participants. For the latter the Connor–Davidson Resilience Scale© was used. Descriptive statistics as well as simple and multiple linear regressions were used in the statistical analysis. Results Of participants, 26.4% reported not having access to personal protective equipment and 50% indicated being concerned for their safety and health. Furthermore, considerable proportions of participants were not satisfied (45%) with the support nor with the appreciation (37.7%) they received during the pandemic. One in four dieticians considered quitting his/her job. While 65.8% of participants reported counseling COVID-19 patients, a third did not use any online platform for counseling. The most cited challenge to dietetic practice during the pandemic was ‘maintaining work-life balance’ (43.1%). The mean CD-RISC score was 72.0 ± 14.0. After adjustment, working in a hospital or public clinic (as opposed to private clinic), having a condition preventing face-to-face counseling, considering quitting job and feeling neutral or dissatisfied with the appreciation were associated with lower resilience scores, while counseling COVID-19 patients was associated with higher scores. Conclusions Despite the fairly high resilience among dieticians practicing in the UAE during the COVID-19 pandemic, the findings of this study highlighted a few challenges, mainly related to safe practice environment, support for online counseling, and maintaining work-life balance. Concerted efforts of policy and decision makers ought to develop targeted programs for dieticians to ensure their retention and wellbeing during the COVID-19 pandemic.